Controlling invasive alien species Vachellia nilotica with triclopyr herbicide in Baluran National Park. Issue 1 (November 2021) - Irianto, R S B; Garsetiasih, R; Setyawati, T; Wahono, N D; Susilo, A; Tjitrosoedirdjo, S
Abstract: Vachellia nilotica ( Acacia nilotica ), as an invasive alien species (IAS), was introduced to Baluran National Park from the Bogor Botanical Gardens in 1969. The purpose was for firebreak to prevent jumping fires from the savanna to the teak forests plantation. However, unexpectedly V. nilotica growth was uncontrollable and invaded the 6000 ha savanna. The rapid growth of this weed has killed the grass in the savanna leading to a decline in the Banteng population in Baluran National Park from 325 in 1998 to 22 in 2011. Since the 1980s, researche on V. nilotica control has been carried out by various universities and research institutions in Indonesia but has not yet obtained an effective and efficient control method. The study aimed to investigate the efficacy of herbicide with the active ingredient of triclopyr by stump brushing to control V. nilotica . Ten triclopyr herbicide concentrations with a solution of diesel and water were tested. The results showed that 1% triclopyr concentration in diesel oil could control 100% of V. nilotica weeds, while water solutions could only control 50% of V. nilotica weeds.